PENANGKAPAN TUNA MADIDIHANG (THUNNUS ALBACARES) DENGAN PANCING ULUR OLEH NELAYAN KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH - Stany R Siahainenia; Ruslan Tawari; Haruna Haruna; Jacobus Paillin; Rifan Dikromo (Pattimura University, 2022)
One of the fishery commodities with high economic value is tuna, where in the Maluku region in 2021, tuna production will be 35.56% (BPS, 2022). Tuna is caught using handlines which are classified as small-scale fisheries. The existence of tuna that changes over time causes fishermen to experience uncertainty in finding suitable fishing areas. Temperature is an important indicator in the distribution and abundance of tuna. This study aims to determine the composition of the hand line catch and to analyze the temperature distribution based on the area of ​​the hand line fishing operation in Central Maluku Regency. The research was conducted in the waters with the method used is a survey method by following fishing trips and using GPS satellite-based Spot Trace to track vessel movement activities during fishing operations. Descriptive data analysis was used to determine the composition of fisherman catches and used SeaWiFS Data Analysis System (SEADAS) 7.3.1 and Surfer 12 to analyze the distribution of water temperatures at fishing locations. The results showed that yellowfin tuna (Thunnus albacares) dominated the catch by 70.30%, bigeye tuna (Thunnus obesus) by 20.19% and skipjack tuna (Katsuwonus pelamis) by 0.52%. The frequency distribution of yellowfin tuna length ranges from 23-171 cmFL where during 2019 it was dominated by sizes <100 cmFL as much as 82.42%. The SST range in January is 290C-310C, optimal fishing is at 29.80C-30.40C, April is in the range of 30.20C-31.70C, optimal fishing is at 30.90C-31.30C, in May is in the range of 27.40C-31,40C the optimal catch is in the temperature range of 27.80C -30.80C, in June is 27.40C -280C the optimal catch is in the temperature range 27.60C-27.850C, in September 27.40C-29.50C the optimal catch is at a temperature range of 27, 80C -28.50C, and in December the range of 29.40C-31.50C is optimal for catching at a temperature range of 30.40C -31.20C